2003
DOI: 10.1152/ajpregu.00326.2002
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of brain angiotensin II to angiotensin III is critical for pressor response in rats

Abstract: The present investigation measured the relative pressor potencies of intracerebroventricularly infused ANG II, ANG III, and the metabolically resistant analogs d-Asp(1)ANG II and d-Arg(1)ANG III in alert freely moving rats. The stability of these analogs was further facilitated by pretreatment with the specific aminopeptidase A inhibitor EC33 or the aminopeptidase N inhibitor PC18. The results indicate that the maximum elevations in mean arterial pressure (MAP) were very similar for each of these compounds acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 51 publications
5
47
0
Order By: Relevance
“…These findings are somewhat unexpected, because increased levels of ang III alter water balance and blood pressure (31)(32)(33). One possible reason why hemodynamics and electrolyte homeostasis remain normal with no APN activity may be that a mouse homologue of the human adipocyte-derived leucine aminopeptidase (A-LAP) can directly cleaves ang II to produce ang IV (34).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat unexpected, because increased levels of ang III alter water balance and blood pressure (31)(32)(33). One possible reason why hemodynamics and electrolyte homeostasis remain normal with no APN activity may be that a mouse homologue of the human adipocyte-derived leucine aminopeptidase (A-LAP) can directly cleaves ang II to produce ang IV (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the brain RAS, Ang III, instead of Ang II, was shown to mediate the pressor response by AT 1 receptors, because selective blockade of the formation of brain Ang III resulted in a decrease in BP. 20 In the kidney, we know that Ang II is converted to Ang III in vivo via aminopeptidase A, which is present in both glomeruli and renal tubules. 4 Ang III is converted to Ang IV via aminopeptidase N. In the lumen of proximal tubule cells, the concentration of Ang II is 1000-fold higher than in plasma, but, because of the high density of peptidases, Ang II only represents Ϸ5% to 15% of total renal Angs.…”
Section: Discussionmentioning
confidence: 99%
“…In the second group, this study was repeated in the presence of a systemic CAND (0.01 mg/kg per minute) infusion 24 hours before and during the experiment. Lastly, the entire experiment was repeated (nϭ17) using higher infusion rates of Ang II (20,40, 80 nmol/kg per minute) in the presence of systemic CAND. Ϫ8 mol/L and Ͼ1ϫ10 Ϫ4 mol/L for AT 2 and AT 1 receptors, respectively), was used interstitially to block the AT 2 receptor.…”
Section: Receptor Blockadementioning
confidence: 99%
“…However, the pressor response to ICV administered D-Asp 1 Ang II in rats after administration of PC18 was not prolonged. 46 Recently, we reported that PC18 and EC33 inhibited the dipsogenic and saline intake responses of rats to an aminopeptidase-resistant Ang II given ICV, and that PC18 delayed the dipsogenic and saline intake responses of rats to an aminopeptidase-resistant Ang III given ICV. 47 This again suggests possible adverse effects of these inhibitors on AT 1 receptor function in the rat brain.…”
Section: Central Effects Of Ang II and Its Aminopeptidase-resistant Amentioning
confidence: 94%